Penyakit Trofoblastik Gestasional: Varian Histopatologi Mola Hidatidosa Vina Amelia1, Ratna Dewi Puspita Sari2 - Vina Amelia; Ratna Dewi PS (CV. Jasa Sukses Abadi, 2020)
Hydatidiform mole is a pathological feature characterized by enlargement of the placental villi. The exact cause is unknown, the incidence of mole varies by race. Hydatidiform mole currently occurs in about 1 in 2000 pregnancies in Europe and the United States, but this case is closer to 1 in 500 in Japan, Singapore, Malaysia or Indonesia. Significant incidence increases of mole have been observed in women after the age of 40 and in women aged below 20. Hydatidiform mole is a common part of gestational trophoblastic disease. Hydatidiform mole can be classified as a benign trophoblast disease. According histologically, the hydatidiform mole is divided into three forms, complete, partial and invasive hydatidiform mole. Mole appears in the first trimester of pregnancy, and usually appears as early pregnancy bleeding. Histopathological examination is the gold standard for diagnosing molar. Complete mole appearance appears as a spontaneous abortion at 8-18 weeks gestation with elevated serum β-human chorionic gonadotropin (β-hCG), partial mole usually occurs at 8-22 weeks gestation and invasive moles have normal or normal serum β-hCG levels. low. Histopathologically, the three are distinguished by the shape of the villus, cistern, trophoblastic inclusions, fetal tissue and trophoblast. In invasive mole bleeding and expansion of molar tissue invasion may occur. Routine histopathological examination after first trimester abortion is to detect ectopic pregnancy or molar pregnancy, which require further treatment.